Formulating Change Management Program to Support ERP Implementation at Weaponry Division, PT Pindad - Dwiartha, Surya; Welly, John (The Indonesian Journal of Business Administration, 2012)
PT Pindad as one of the State Owned Enterprises in Indonesia, manufacturing the defense and security equipment recently conducting change in their business system by implementing Enterprise Resource Planning in the Weaponry Division. To support the implementation of ERP, it should be accompanied by good change management program. However current change management program seems to ignore the implementation stages features in Kotter 8-Steps. Anticipating this condition, the author suggesting Kotter 8-Steps as a basic framework of research. The findings from FGD and in-depth interview shows that Step-3: Creating a Vision, Steps-4: Communicating Vision for Buy-in and Step-5: Empowering Action had not been done systematically causing the possibility of failure looming large. To support the analysis, STAR Model of organization, Strategy Map, and DICE Framework were being used to fill the void on the Kotter Program. However, PT Pindad had not done Kotter’s Step-6 to Step-8 because the change management process was still in the preliminary phase. Keywords: PT. Pindad, change management, strategy map, STAR model organizational design, DICE framework